Emotional burnout as contributor to negative personality changes in professional athletes - Koretskaya, I. A.; Dneprovskaya, N. V.; Shevtsova, I. V.; Mikhailovsky, M. N. (Theory and Practice of Physical Culture, 2017)
Objective of the study was to analyse the effects of emotional burnout on the social adaptability of handball players. We applied a variety of research methods at different stages of the study as dictated by the relevant goals including: theoretical and practical data analysis; diagnostic self-tests; and V.V. Boyko`s Emotional Burnout Test; with the test data being statistically processed using the Mann-Whitney U-criterion. The experiments and psychological tests under the study were performed at the Moscow Handball Federation. Subject to the study were 62 professional handball players of 17-24 years of age split up into two groups: with and without indications of an emotional burnout. The subjects were tested to rate their personal mental statuses. The study data and analyses gave the grounds to confirm that an emotional burnout causes a negative impact on the professional efficiency of athletes. Both of the groups of the subjects were tested with different personality qualities. The emotional burnout syndrome (EBS) was found to contribute to the negative personality changes that, in their turn, are detrimental to the social adaptation.